Requalification of a Brazilian Trichoderma collection and screening of its capability to decolourise real textile effluent - Lisboa, Dianny Silva (2017)
Water contamination with large amounts of industrial textile coloured effluents is an environmental concern. For the treatment of textile effluents, white-rot fungi have received extensive attention due to their powerful capability to produce oxidative (e.g., ligninolytic) enzymes. In addition, other groups of fungi, such as species of Aspergillus and Trichoderma, have also been used for textile effluents treatment. The main aim of the present study was to requalify a Brazilian Trichoderma culture collection of 51 Trichoderma strains, isolated from different sources in Brazil and preserved in the oldest Latin-American Fungal Service Culture Collection, The Micoteca URMWDCM 804 (Recife, Brazil). Fungal isolates were re-identified through a polyphasic approach including macro- and micro-morphology and molecular biology, and screened for their capability to decolourise real effluents collected directly from storage tanks of a textile manufacture. Trichoderma atroviride URM 4950 presented the best performance on the dye decolourisation in real textile effluent and can be considered in a scale-up process at industrial level. Overall, the potential of Trichoderma strains in decolourising real textile dye present in textile effluent and the production of the oxidative enzymes Lac, LiP and MnP was demonstrated. Fungal strains are available in the collection e-catalogue to be further explored from the biotechnological point of view.